Clinical study of conservative and surgical management of blunt abdominal trauma: a prospective observational study - Mujawar, Parvez; Sabir, Kothawala Sadikali; Bagwan, Asif (International Journal of Research in Medical Sciences, 2025)
Background: Blunt abdominal trauma represents a significant cause of morbidity and mortality, particularly in developing countries. The management approach has evolved from primarily surgical to selective non-operative management in hemodynamically stable patients. Methods: A prospective observational study was conducted at a tertiary care center over 18 months, including 50 patients with blunt abdominal trauma. Data were collected on demographics, clinical presentation, management approach, and outcomes. Statistical analysis was performed using chi-square test and Student’s t-test. Results: The study included 40 males (80%) and 10 females (20%), with mean age of 35.2 years. Road traffic accidents accounted for 50% of cases, followed by assault (38%) and falls (12%). Surgical management was required in 31 patients (62%), while 19 patients (38%) were managed conservatively. The overall mortality rate was 10% (5 patients), with 90% achieving complete recovery. Mesenteric tears were the most common intraoperative finding (60% of surgical cases). Significant associations were found between outcome and clinical features including abdominal distension (p=0.026), vomiting (p=0.045), and associated injuries (p=0.023). Conclusions: Blunt abdominal trauma predominantly affects young males, with road traffic accidents being the leading cause. While surgical intervention remains necessary in the majority of cases, selective non-operative management can be safely applied in hemodynamically stable patients with appropriate monitoring. Early recognition and prompt intervention are crucial for optimal outcomes.